Creative Industries and Their Effects on Local Economic Development Job Creation and Innovation - Mulyasari, Indira; Suparlin, Alam; Rusli, Rusli (Journal Development Manecos, 2024)
This research seeks to establish the creative industries’ position in the creation of creativity-based local economic development through quantitative research. The creative industries are those that involves sectors like arts, design, media and the communication, fashion, architecture, technology, and advertisement among others. The research used a structured questionnaire administered on the respondents in these sectors to obtain empirical evidence on their contribution to the economy, employment generation, innovation and issues affecting them. The data showed that creative industries make considerable impacts on local economic development with respect to employment generation and innovativeness that has digital change as a major determinant. Enriching economic performance was also found to be positively influenced by cross-sector knowledge spillovers between the creative disciplines with the rest sectors. Thus, the major threats, which were described by the respondents, were the following: limited access to the financing, shortage of skills for development, and infrastructure constraints. Such a study implies the need to mapped and address the potentials and barriers of creative industries through a policy that focuses on digital environment and skills. By so doing, stakeholders are able to build on sustainability and improve the creative sectors in order to have increases impact in the local economy. This paper’s main value therefore lies in presenting quantifiable data on the economic impacts of the creative industries and recommendations for practice that may be useful to policy makers and business strategists.